Emergency Services Workforce 2030: Changing landscape literature review - McLennan, Blythe; Chong, Jane; Dunlop, patrick (Bushfire and Natural Hazards CRC, 2022)
The Changing Landscape Literature Review collates a high-level evidence base around seven major themes in the changing landscape (i.e., the external environment) that fire, emergency service, and rural land management agencies operate in, and which will shape workforce planning and capability requirements over the next decade. It is an output of the Workforce 2030 project and is one of two literature reviews that summarise the research base underpinning a high-level integrative report of emerging workforce challenges and opportunities, Emergency Services Workforce 2030.